Pregnancy complicated with diabetes - Pacora Portella, Percy (2015)
We show how diabetes mellitus complicates pregnancy and what are the risks these patients and their newborns are exposed to. For this purpose the experience of Hospital San Bartolomé was revised. From January 1972 to December 1989, 56,347 pregnant women attended for pre-natal care, 11,298 (20%) women had diabetes risk factors and underwent oral glucose tolerance (OGIT) according to conventional criteria 538 patients were identified as pregnancy complicated by diabetes (GDM). Mean age was 31 y.o. (DS ± 6,5). 525 GDM (97,6%) were gestational diabetes (GD) and 13 (2,4%) pregestational diabetes (PGD). These latter were older than GD (p<0,05). 54 patients were lost (10%) and did riot deliver at the hospital. GDM women had significant maternal and perinatal complications in comparison to the total pregnant population (p<0,005). Considering abnormal plasma fasting glucose ³ 80 mg/dl (4,5 mM/L), we would detect 500 GDM patients (93%) at the first visit. Although pre-natal care diminishes maternal risks, perinatal morbimortality is still high in our country; this is especially true in PGD. Thus, we recommend the prompt detection of these patients for the multidisciplinary assistance.